SAT0324 Certolizumab pegol provides sustained remission and minimal disease activity in patients with psoriatic arthritis over 4 years' treatment. (12th June 2018) - van der Heijde, D.; Deodhar, A.; FitzGerald, O.; Fleischmann, R.; Gladman, D.; Gottlieb, A.B.; Coates, L.C.; Hoepken, B.; Bauer, L.; Peterson, L.; Khraishi, M.; Mease, P.J.
Abstract : Background: Disease Activity Index for Psoriatic Arthritis (DAPSA) 1 and the minimal disease activity (MDA) criteria 2 are instruments recommended for evaluating disease activity in psoriatic arthritis (PsA). The RAPID-PsA trial (NCT01087788 ) has demonstrated the sustained efficacy of certolizumab pegol (CZP) across the spectrum of PsA symptoms. 3, 4 Objectives: To report the proportion of CZP-treated patients (pts) achieving DAPSA remission (REM), DAPSA low disease activity (LDA), MDA (fulfilling ≥5/7 MDA criteria), and very low disease activity (VLDA; fulfilling 7/7 MDA criteria) over 216 weeks (wks) in RAPID-PsA. Methods: RAPID-PsA was double-blind and placebo-controlled to Wk24, dose-blind to Wk48, and open-label (OL) to Wk216. Pts had active PsA and had failed ≥1 disease modifying anti-rheumatic drug. Data for pts randomised to CZP at Wk0 (200 mg every 2 wks or 400 mg every 4 wks, following a 400 mg loading dose at Wks0, 2, 4), who continued their assigned dose in the OL period, are presented as observed case and with imputation (figure 1). Outcomes reported are DAPSA (the sum of tender and swollen joint counts [TJC 68; SJC 66], pt global and pain assessment [10 cm visual analogue scale], and C-reactive protein levels [mg/dL]), and pts achieving: 1) DAPSA LDA (DAPSA>4 and≤14); 2) DAPSA REM (DAPSA≤4); 3) MDA (fulfilling ≥5/7 MDA criteria); and 4) VLDA (fulfilling 7/7 MDA criteria), to Wk216. Pts withdrawing from the study between scheduled visits had their final observed assessment values assigned to the next scheduled visit timepoint. Results: Of 409 pts randomised; 273 received CZP from Wk0, of whom 248 (90.8%) completed Wk24, 237 (86.8%) completed Wk48, and 183 (67.0%) completed Wk216. The mean (SD) baseline DAPSA was 44.8 (22.9). Of pts completing Wk24, 29.7% (74/249) achieved LDA; 25.3% (63/249) REM; 38.2% (95/249) MDA; and 14.9% (37/249) VLDA. At Wk216, 31.9% (59/185) achieved LDA; 44.3% (82/185) REM; 57.8% (107/185) MDA; and 29.0% (58/183) VLDA (figure 1). Conclusions: A substantial proportion of pts who completed the 4 year study achieved disease inactivity targets:~75% achieved DAPSA LDA or REM, almost 60% achieved MDA, and half of those also achieved VLDA. References: [1] Schoels MM. Ann Rheum Dis2016;75(5):811–18. [2] Coates LC. Ann Rheum Dis2010;69(01):48–53. [3] Mease PJ. Ann Rheum Dis2016;75:608. [4] FitzGerald O. JAAD2017;76(6):AB264. Acknowledgements: This study was funded by UCB Pharma. We thank the patients and their caregivers in addition to the investigators and their teams who contributed to this study. Editorial services were provided by Costello Medical. Disclosure of Interest: D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Daiichi, Eli Lilly, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi-Aventis, UCB Pharma, Employee of: Director of Imaging Rheumatology B.V., A. Deodhar Grant/research support from: AbbVie, Amgen, Eli Lilly, GlaxoSmithKline, Janssen, Novartis, Pfizer, UCB Pharma, Consultant for: Eli Lilly, Janssen, Novartis, Pfizer, UCB Pharma, O. FitzGerald Grant/research support from: AbbVie, Bristol-Myers Squibb, Janssen, Pfizer, Consultant for: AbbVie, Celgene, Amgen, Eli Lilly, Janssen, Pfizer, UCB Pharma, Speakers bureau: AbbVie, Celgene, Janssen, Novartis, Pfizer, UCB Pharma, R. Fleischmann Grant/research support from: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celgene, Eli Lilly, Genentech, Janssen, MSD Pharmaceuticals, Novartis, Pfizer, Roche, Sanofi-Aventis, UCB Pharma, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Eli Lilly, GlaxoSmithKline, Janssen, Novartis, Pfizer, Sanofi-Aventis, D. Gladman Grant/research support from: Abbott, Amgen, Bristol-Myers Squibb, Celgene, Johnson and Johnson, MSD, Novartis, Pfizer, UCB Pharma, Consultant for: Abbott, Bristol-Myers Squibb, Celgene, Johnson and Johnson, MSD, Novartis, Pfizer, UCB Pharma, A. Gottlieb Grant/research support from: Abbott, Aclaris, Actelion, Akros, Amiscus, Amgen, Astellas, Baxalta, Beiersdorf, Bristol-Myers Squibb, Canfite, Catabasis, Celgene, Coronado, Crescendo Bioscience, CSL Behring Biotherapies for Life, Dermipsor, Dermira, Eli Lilly, Genentech, GlaxoSmithKline, Incyte, Janssen, Karyopharm, KinetaOne, KPI Therapeutics, Levia, Meiji Seika Pharma Co., Merck, Mitsubishi Tanabe, Novartis, Novo Nordisk, Pfizer, Reddy, Takeda, TEVA, UCB Pharma, Vertex, Xenoport, Consultant for: Abbott, Aclaris, Actelion, Akros, Amiscus, Amgen, Astellas, Baxalta, Beiersdorf, Bristol-Myers Squibb, Canfite, Catabasis, Celgene, Coronado, Crescendo Bioscience, CSL Behring Biotherapies for Life, Dermipsor, Dermira, Eli Lilly, Genentech, GlaxoSmithKline, Incyte, Janssen, Karyopharm, KinetaOne, KPI Therapeutics, Levia, Meiji Seika Pharma Co., Merck, Mitsubishi Tanabe, Novartis, Novo Nordisk, Pfizer, Reddy, Takeda, TEVA, UCB Pharma, Vertex, Xenoport, L. Coates Grant/research support from: AbbVie, Janssen, Novartis, Pfizer, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Prothena, Sun Pharma, UCB Pharma, B. Hoepken Employee of: UCB Pharma, L. Bauer Employee of: UCB Pharma, L. Peterson Employee of: UCB Pharma, M. Khraishi Grant/research support from: Abbott, Amgen, Pfizer, Consultant for: Abbott, Amgen, Pfizer, P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer, Sun, UCB Pharma, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer, Sun, UCB Pharma, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer, UCB Pharma